1992
DOI: 10.1002/zaac.19926120116
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung und spektroskopische Charakterisierung des Clusteranions [(Mo6Cl8i)(CF3COO)6a]2−

Abstract: Bei der Umsetzung von [(Mo6Cl 8i)Cl 6a]2− in Dichlormethan mit Trifluoressigsäure entsteht in der Siedehitze unter Freisetzung von HCl das neue stabile Clusteranion [(Mo6Cl 8i)(CF3COO) 6a]2−. Die zentrale (Mo6Cl8i)‐Gruppe wird bei der Reaktion nicht angegriffen. Bei der 19FNMR‐Messung zeigt ein im Vergleich zum freien CF3COO− tieffeldverschobenes Singulett die Äquivalenz aller Trifluoracetatliganden an, deren einzähnige Koordination am Cluster aus charakteristischen Lagen der IR‐Frequenzen der Carboxylgruppen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…The excitation spectrum recorded for this emission band (monitored at λ = 635 nm) reveals several bands with maxima at λ = 280 (4.43 eV), 335 (3.70 eV), 435 (2.85 eV), and 490 nm (2.53 eV). These emission‐band profiles and the large Stokes shift of 1.27 eV of (TBA) 2 [W 6 I 8 (O 3 SC 7 H 7 ) 6 ] are similar to those reported for (TBA) 2 [W 6 I 8 (CF 3 COO) 6 ] and the corresponding Mo cluster compounds , …”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The excitation spectrum recorded for this emission band (monitored at λ = 635 nm) reveals several bands with maxima at λ = 280 (4.43 eV), 335 (3.70 eV), 435 (2.85 eV), and 490 nm (2.53 eV). These emission‐band profiles and the large Stokes shift of 1.27 eV of (TBA) 2 [W 6 I 8 (O 3 SC 7 H 7 ) 6 ] are similar to those reported for (TBA) 2 [W 6 I 8 (CF 3 COO) 6 ] and the corresponding Mo cluster compounds , …”
Section: Resultssupporting
confidence: 83%
“…Solution reactions of (TBA) 2 [Mo 6 Cl i 8 Cl a 6 ] (TBA = tetrabutylammonium) revealed that the outer ligands are more loosely bound to the cluster than the inner (face‐capping) ones. As a consequence, they can be exchanged readily in transmetalation reactions with silver salts, as has been shown for (TBA) 2 [Mo 6 Cl 8 (CF 3 COO) 6 ] . More recently, several molybdenum iodide compounds, for example, (TBA) 2 [Mo 6 I 8 (C 3 F 7 COO) 6 ] and (TBA) 2 [Mo 6 I 8 (CF 3 COO) 6 ], were reported to show remarkably enhanced photophysical properties.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations